Numerical modelling and simulation of dielectrophoretic based WBC sorting using sidewall electrodes - Yousuff, C.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
With the advancement in microfluidic 'lab on a chip' systems, a mechanism to continuously separate submicron particles is needed. Dielectrophoresis (DEP) is a method that has demonstrated great potential in cell discrimination and isolation from mixture of many heterogeneous samples by utilizing the electrical properties of particles/cells and the medium. Here, we present a numerical model and simulation of microfluidic device with sidewall electrodes which generates non uniform field along the width of the micro channel to produce require negative DEP force which deflects the White Blood cells (WBC) from the sidewall to targeted outlet and red blood cells (RBCs) remain focused and followed the direction of the fluid flow and collected at waste outlet. We witnessed that, WBCs are separated with 100 efficiency from cell mixture at an applied voltage of 6 V with flow rate 0.2uL/min. © 2016 IEEE.